Systematic characterisation of disease associated balanced chromosome rearrangements by FISH: cytogenetically and genetically anchored YACs identify microdeletions and candidate regions for mental retardation genes. Issue 4 (1st April 1999) - Wirth, J; Nothwang, H-G; van der Maarel, S; Menzel, C; Borck, G; Lopez-Pajares, I; Brøndum-Nielsen, K; Tommerup, N; Bugge, M; Ropers, H-H; Haaf, T
Abstract : Disease associated balanced chromosome rearrangements (DBCRs) have been instrumental in the isolation of many disease genes. To facilitate the molecular cytogenetic characterisation of DBCRs, we have generated a set of >1200 non-chimeric, cytogenetically and genetically anchored CEPH YACs, on average one per 3 cM, spaced over the entire human genome. By fluorescence in situ hybridisation (FISH), we have performed a systematic search for YACs spanning translocation breakpoints. Patients with DBCRs and either syndromic or non-syndromic mental retardation (MR) were ascertained through the Mendelian Cytogenetics Network (MCN), a collaborative effort of, at present, 270 cytogenetic laboratories throughout the world. In this pilot study, we have characterised 10 different MR associated chromosome regions delineating candidate regions for MR. Five of these regions are narrowed to breakpoint spanning YACs, three of which are located on chromosomes 13q21, 13q22, and 13q32, respectively, one on chromosome 4p14, and one on 6q25. In two out of six DBCRs, we found cytogenetically cryptic deletions of 3-5 Mb on one or both translocation chromosomes. Thus, cryptic deletions may be an important cause of disease in seemingly balanced chromosome rearrangements that are associated with a disease phenotype. Our region specific FISH probes, which are available to MCN members, can be a powerful tool in clinical cytogenetics and positional cloning.